Technology entrepreneurship : creating, capturing and protecting value - Duening, Thomas N.; Hisrich, Robert D.; Lecthter, Michael A. (Academic Press, 2010)
Focuses on intellectual property development, funding, and marketing/selling. This book provides a treatment of valuation, deal structuring, and equity preservation issues. It discusses technology management and continuous innovation as a competitive advantage. It addresses the issue of leading, managing, and compensating technical workers